(untitled) (Research, Society and Development, 2021)
This work aimed to study the potential of dry residue from jabuticaba bark (Myrciaria cauliflora) as a substrate in the production of exo-polygalacturonase (Exo-PG) through solid state fermentation (FES) using the microorganism Aspergillus niger CCT 0916 as a fermentation agent. The jabuticaba peels were dried in an oven with air circulation at 55 ºC with an air speed of 1.0 m/s and then crushed to obtain the dry residue, which was characterized. A solid state fermentation was carried out in the period from 0 to 72 hours, during this period the following parameters were analyzed: moisture of the medium, pH, reducing sugars and polygalacturonic activity (APG). High levels of reducing sugars and pectin were found in the dry residue of the jabuticaba bark (RSJ). The adsorption isotherms showed that the adequate water activity for the fermentation process must be above 0.7. The maximum peak of APG was 16.12 U/g of the fermented medium reached in 72 h of culture, therefore this residue is potentially viable as a substrate in the synthesis of Exo-PG by solid state fermentation.